Optimally locating electric scooter battery swapping stations and battery deployment. Issue 5 (4th May 2021) - Yan, Shangyao; Lin, Chih-Kang; Kuo, Zong-Qi
ABSTRACT: In the past, several studies have focused on planning for the deployment of charging stations for electric vehicles, with fewer studies being conducted on electric scooters. These works, however, did not consider the characteristics of electric scooters with regard to tourism activities. Therefore, in this study the authors adopt network flow and mathematical programming techniques to develop a model to find the optimal location for electric scooter battery swapping stations and battery deployment. This model is formulated as an integer network flow problem with side constraints and is characterized as NP hard. To efficiently and effectively solve the model for large-scale problems faced in practice, a solution algorithm is also developed. Finally, numerical tests are conducted using real data for Taichung City, Taiwan. The results demonstrate that the proposed model and solution algorithm are potentially useful for locating battery swapping stations and battery deployment in actual practice.